Anxiety-related psychological impacts in the COVID-19 pandemic on cardiovascular diseases and diabetes - Teixeira, Lucas (2020)
Patients and the general public are under insurmountable psychological pressure which may lead to various psychological problems, such as anxiety, fear, depression, and insomnia, causing, consequently, the impaired quality of life. Psychological crisis intervention plays a pivotal role in the overall deployment of health-related quality of life and disease control. A novel Severe Acute Respiratory Syndrome Coronavirus-2 (SARSCoV-2), a pathogen of the new coronavirus disease (COVID-19), has affected several sector activities, including people's health. To enhance infection control methods, appropriate interventions, and public health policies, the present study aims to assess the fear and peri-traumatic stress during the Covid-19 in Brazil. Method: A cross-sectional survey has been conducted from April 12th to 18th using the Peri-Traumatic Distress Scale (CPDI) and the Fear Scale (FCV-19S) aiming to measure the peri-traumatic stress and fear as psychological reactions during the COVID-19 pandemic. For that purpose, an online spreadsheet was used to send the questionnaire and scales to a sample of 1844 participants as a collecting information tool. After the data analysis, the individuals were separated into 4 groups: Group 1 (1232) population without chronic health conditions; group 2 (298) patients with previous psychological suffering, group 3 (229) patients with cardiovascular diseases, group 4 (71) patients with diabetes. For analysis, G1 and were considered control for comparison with groups 2, 3 and 4 in accordance with One-Way Anova followed by Bonferroni test. Results: All the groups showed the CPDI and FCV-19S increased in comparison with the G1 group. Concerning CPDI, the G 3 was increased when compared to G1, G2 and G4. The G3 had the FCV-19S higher in comparison with G1, G2 and G4. The Wilcoxon-Mann-Whitney test showed a statistical difference between the control group in comparison with 2 and 3 groups (Mann-Whitney p< 0.05). Conclusion: The COVID-19 pandemic had a significant impact on the Brazilian population, with patients with heart disease and hypertension presenting the highest numbers of stress and fear, with numbers comparable and even higher than those who reported previous psychological distress.